2017
DOI: 10.1002/polb.24426
|View full text |Cite
|
Sign up to set email alerts
|

Spin‐labeling of polymeric micelles and application in probing micelle swelling using EPR spectroscopy

Abstract: Polymer structure and conformational dynamics are essential to polymer macroscopic properties, but are challenging to probe. We report here a synthetic pathway to chemically add a nitroxide moiety onto block polymers in a mild, aqueous environment and demonstrate its use in a series of polymeric micelles using Electron Paramagnetic Resonance (EPR) spectroscopy. The micelles were characterized with several analytical approaches and EPR findings were in general consistent with other approaches. Upon exposure to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…The fact that the labeled HA peptide shows three sharp lines regardless of the solvent indicates that the labels within one peptide molecule are separated by at least 10 Å; otherwise dipole−dipole interactions between nearby labels would cause additional line broadening to the CW EPR spectrum. 25 The concentration of the labeled peptide was estimated based on the spin concentration reported by the double integrated EPR spectral intensity via a calibration method (see the SI and Figure S3). The stock solution of the spin labeled HA peptide in this work was 8.16 mM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that the labeled HA peptide shows three sharp lines regardless of the solvent indicates that the labels within one peptide molecule are separated by at least 10 Å; otherwise dipole−dipole interactions between nearby labels would cause additional line broadening to the CW EPR spectrum. 25 The concentration of the labeled peptide was estimated based on the spin concentration reported by the double integrated EPR spectral intensity via a calibration method (see the SI and Figure S3). The stock solution of the spin labeled HA peptide in this work was 8.16 mM.…”
Section: Resultsmentioning
confidence: 99%
“…While Nuclear Magnetic Resonance (NMR) spectroscopy has been used to probe the “host–guest” interaction in IMAs, the background signals of micelles limit the selective determination of peptide dynamics. Electron Paramagnetic Resonance (EPR) in combination with Site-Directed Spin Labeling (SDSL) has been proved to be powerful in determining otherwise inaccessible structural information in complex biological systems. SDSL relies on attaching an EPR active spin label to the target biomacromolecules, especially a peptide/protein, at a residue that reacts specifically with the labeling compound. Typical information from EPR is the site-specific backbone dynamics of the labeled site, which is dependent on and reports the local environment (crowding, polarity) of macromolecular systems. , …”
Section: Introductionmentioning
confidence: 99%
“…However, due to the low selectivity and sensitivity of most mainstream analytical techniques, there are some limitations in understanding the molecular-level interactions . To study the molecular interactions and dynamics in nanostructured materials’ interfaces, we used a highly selective and sensitive electron paramagnetic resonance (EPR) spectroscopy. , EPR spectroscopy is a promising and tailor-made technique for the study of microenvironments and dynamic phenomena of colloidal systems. Various studies were reported on the internal dynamics and local structure of radical-associated nanostructures using EPR spectroscopy by investigating the line shape changes. The rotational dynamics of the radical-containing covalent linkage position and the side groups in the polymer chain significantly reflect the local dynamics of polymer assembly. For example, by considering the hydrogen bonding tendencies, Ortony et al used EPR spectroscopy to report the local dynamics of supramolecular nanofibers in the assembly structure . EPR spectroscopy provides quantitative evidence of the rotational dynamics, inter and/or intramolecular distance between the radicals, solvent accessibility, and micropolarity of the immediate environment.…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38][39][40][41][42][43][44][45][46] Recently,wehave reported EPR in probing structural insights at the complex nano-bioi nterfaces [47,48] and in polymeric micelles. [49] EPR can probe structural information in the native stateo ft he target system,r egardless of thes ize and complexity.I na ddition, once spin labeled, the hybrid's concentrationi sp roportional to the spin concentrationw hich is immune of any complications caused by polymer optical ab-Protein-polymer conjugates are attractive biomaterials which combine the functions of both proteins and polymers. The bioactivity of these hybrid materials, however, is often reduced upon conjugation.…”
Section: Introductionmentioning
confidence: 99%
“…EPR has been widely used in probing structure and conformational dynamics in complex, large biological or polymeric systems . Recently, we have reported EPR in probing structural insights at the complex nano‐bio interfaces and in polymeric micelles . EPR can probe structural information in the native state of the target system, regardless of the size and complexity.…”
Section: Introductionmentioning
confidence: 99%